2017
DOI: 10.1111/radm.12257
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of green innovations – The impact of stakeholders and their network relations

Abstract: Green innovation is becoming increasingly important for companies and whole societies, and the research in this field has essentially increased in recent years. As green innovation is expected to ensure both environmental sustainability and economical profitability, it might seriously affect the partly colliding interests of various groups of stakeholders. However, from previous studies less is known about the impact that various groups of stakeholders and particularly the relationships among these stakeholder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 48 publications
0
60
0
Order By: Relevance
“…In recent times, there has been a strong drive towards sustainable‐oriented innovation products and services (Schiederig et al ., ; Ketata et al ., ; Fliaster and Kolloch, ) with such descriptors as ‘green’ or ‘environmentally friendly’. There are three reasons for such change: the impact of new sustainable technologies (Dubey et al ., ); government policies and legislation leading to new environmental process standards (ISO 9000 and ISO 14000); changes in social attitudes within society (Brundtland, ).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent times, there has been a strong drive towards sustainable‐oriented innovation products and services (Schiederig et al ., ; Ketata et al ., ; Fliaster and Kolloch, ) with such descriptors as ‘green’ or ‘environmentally friendly’. There are three reasons for such change: the impact of new sustainable technologies (Dubey et al ., ); government policies and legislation leading to new environmental process standards (ISO 9000 and ISO 14000); changes in social attitudes within society (Brundtland, ).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…The outcome of such pressures has been for some firms to adopt and/or develop innovations that are oriented towards delivering increased sustainability (Nidumolu et al ., ). However, such changes at the level of the firm do not just happen: they require the organizational culture of the firm to become more responsive to sustainability issues and pressures (Fliaster and Kolloch, ) and, in some firms, to take the initiative with a significant change in organizational culture with regard to becoming more ‘sustainability oriented’ (Denham and Kaberon, ). Such organizational culture change initiatives may require firms to become more innovative (Kyrgidou and Spyropoulou, ; Ketata et al ., ).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Aguilera-Caracuel and Ortiz-de-Mandojana [175] and Dangelico [176] explained that the intensity of green innovation is positively related to firm profitability. Fliaster and Kolloch [177] researched green innovation and found that it is likely to be affected by the interactions between primary and secondary stakeholders and it is further expected to ensure profitability. In addition, there is evidence that innovation in the products and processes of companies generates social, organizational, and financial results [93,178,179].…”
Section: Innovation and Profitabilitymentioning
confidence: 99%
“…Aguilera-Caracuel and Ortiz-de-Mandojana [152] and Dangelico [153] explained that the intensity of green innovation is positively related to firm profitability. In reality, Fliaster and Kolloch [154] researched green innovation and found that it is likely to be affected by the interactions between primary and secondary stakeholders and, it is further expected to ensure profitability. In addition, there is evidence that innovation in the products and processes of companies generates social, organizational, and financial results [77,155,156].…”
Section: Innovation and Profitabilitymentioning
confidence: 99%